Handbook of engaged scholarship : contemporary landscapes, future directions, volume 2 : community-campus partnerships - Fitzgerald, Hiram; Burack, Cathy; Seifer, Sarena D. (Handbook of engaged scholarship., 2010)
Annotation In the preface to theHandbook of Engaged Scholarship, Hiram Fitzgerald observes that the Kellogg Commission's challenge to higher education to engage with communities was a significant catalyst for action. At Michigan State University, the response was the development of "engaged scholarship," a distinctive, scholarly approach to campus-community partnerships. Engaged scholars recognize that community based scholarship is founded on an underpinning of mutual respect and recognition that community knowledge is valid and that sustainability is an integral part of the partnership agenda. In this two-volume collection, contributors capture the rich diversity of institutions and partnerships that characterize the contemporary landscape and the future of engaged scholarship. Volume One addresses such issues as the application of engaged scholarship across types of colleges and universities and the current state of the movement. Volume Two contains essays on such topics as current typologies, measuring effectiveness and accreditation, community-campus partnership development, national organizational models, and the future landscape.